Developing Intercultural Competence in Higher Education: International Students’ Stories and Self-Reflection - Sabet , Peyman G. P.; Chapman, Elaine (Journal of International Students, 2023)
Developing Intercultural Competence in Higher Education: International Students’ Stories and Self-Reflection is a timely publication based on an innovative methodology called the UNESCO Story Circles. To facilitate the development of intercultural competence, the book draws on the analysis and reflection on the lived experiences of international students from diverse backgrounds. It provides valuable insights for not only students but also educators and practitioners involved in international education.